Innovation and Collaboration in the Digital Era The Role of Emotional Intelligence for Innovation Leadership and Collaborative Innovation - Pascual, Jara (Business & economics, 2021)
Innovation and Collaboration in the Digital Era provides a holistic approach to collaborative innovation, innovation management and innovation leadership. It is full of practical advice and includes 34 interviews with high-level politicians, innovation industry leaders, academics and entrepreneurs discussing the reality of innovation and how to create change for a positive impact. Many "es are included from researchers and practitioners in the innovation field who have participated as guests in the author's podcast "Business of Collaboration" or in interviews with the Collabwith Magazine which she produces. This is a powerful book full of practical frameworks and one-page canvases which act as reminders of the value of making needs and expectations explicit. The author provides frameworks and tools that can be used to support collaboration journeys across different sectors and organizations. She also offers clarity to the reader for their innovation journey and brings a new perspective on how to innovate and understand innovation. Jara Pascual focuses on the importance of managing emotions and feelings of frustration which can be very common during a collaborative innovation process. She explores the interaction between Emotional Intelligence and business and shows how to remove and manage frustration and how to produce a positive outcome. Innovation and Collaboration in the Digital Era will empower the reader to take action and show how to change your conversation about innovation and collaboration.‹/EM› "Innovation and collaboration are among the most important concepts that drive human society forward. Jara Pascual explores their interplay in a unique way, with the chapters walking through the richness of the topics like a Mediterranean food market, full of colour, diversity and flavours. A remarkable, engaging and satisfying read." Johan Kestens, CIO New York Mellon Bank "Jara's voice is rigorous and inspiring on how to manage organizations in the current era. Inded, there are strategic reasons for diversity. And indeed, good leaders are not just smart, but emotionally intelligent. A MUST READ!" Elena Arrieta, tech & innovation journalist. Currently working as Communications Manager at DigitalES, the Spanish Association for Digitalisation. "Jara Pascual is opening a new box for innovation. I was intrigued about the connection of Emotional Intelligence and business in particular in a startup context. Everyone is looking for recipes for personal and professional success and this approach might be the key for both." Sabine Stuiver, Co-founder and CMO Hydraloop "Jara Pascual, with colleague Celia Avila-Rauch, has been able to distill and apply the ability model of emotional intelligence to the art and science of innovation and innovation leadership. In our work we note that feelings are not always facts but that emotions as a form of data. More than that, emotions can assist or facilitate with decision making, creativity and innovation rather than getting in the way, but only if leaders are "smart" about emotions and develop and deploy their emotional intelligence skills." Dr David R Caruso, Emotional Intelligence Skills Group, Founder Yale Center for Emotional Intelligence, Research Affiliate.